Renewing polyethylene: insertion copolymerization of sugar derived hydrophilic monomers with ethylene - Rajput, Bhausaheb S.; Pawal, Sandip B.; Bodkhe, V. Dnyaneshwar; Rao, I. Nagamalleswara; Sainath, Annadanam V. Sesha; Chikkali, Samir H. (European Polymer Journal, 2020)
Although highly desirable, insertion copolymerization of renewable resource derived functional olefins with ethylene has been rarely investigated. Herein, we report insertion copolymerization of challenging sugar derived isohexide mono-enes with ethylene in the presence of Pd-phosphinesulfonate acetonitrile catalyst (C1). Thus, copolymerization of ethylene with isomannide mono-ene (2a), isosorbide mono-ene (2b'), isoidide mono-ene (2c) and methacryl-2,3,4,6-tetra-O-acetyl-D glucopyranoside (2d) afforded corresponding functionalized polyethylene (P2a-1 to P2d-1). High temperature proton NMR investigations revealed enchainment of 2a-2c in polyethylene backbone and the highest incorporation of 1.45% was observed for 2c. The high temperature proton NMR results were further corroborated by solid state C-13 NMR and IR spectroscopy. Gel permeation chromatography analysis displayed weight average molecular weight in the range of 13.0-27.2 x 10(3) g/mol. The thus prepared copolymers revealed melting temperature in the range of 117-126 degrees C. Relatively reduced melting temperature compared to neat polyethylene may suggest an irregular arrangement of pendant functional group on polyethylene main chain.
Keywords: Hydrophilic polyethylene; insertion copolymerization; Isohexide mono-enes; Polyethylene; Sugar